Analysis of Effective Professionalism Relationships With Interprofessional Attitudes Through Outbound Activities: Literature Review - Mahendra, Alfian Ihza; Kurniawati, Anerinanta Ajeng Nurul; Mawarni, Briza Tris; Rahayu, Dinarsih; Fa’izah, Erika Nur; Amalina, Haliza; Fanani, Erianto; Soares, Domingos (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
Introduction: Professional medical personnel must have elements of professionalism, basic principles of medicine and professional ethics in carrying out their profession. Integrity is one of the professional values mentioned in the Professional Medical Personnel Association's Code of Ethics. This is defined as a commitment to her five core values of integrity, trust, equality, respect, and accountability. Method: This article is a systematic review of the literature. References are examined to see whether they fulfill the following criteria: Ten-year source limitation, publication in English and Indonesian, and open access to abstracts and papers. Writing this article uses 10 literature studies and searches databases from Sciencedirect, Pubmed, Google Scholar and other related journals from 2018 to 2023 with keyword syntax for each database. Result: Of the ten literatures used in the literature review, it shows that a medical worker must have elements of professionalism, teamwork, and professional ethics in carrying out his work. Conclusion:Characteristics that a professional should have, especially in the field of medical personnel are teamwork, honesty, professionalism, and integrity.